Melting Hadrons, Boiling Quarks: From Hagedorn Temperature to Ultra-Relativistic Heavy-Ion Collisions at CERN: With a Tribute to Rolf Hagedorn - Rafelski, Johann (Cham Springer Nature, 2016)
Nuclear Physics, Heavy Ions, Hadrons; History and Philosophical Foundations of Physics; Particle Acceleration and Detection, Beam Physics; History of Science
English
Keywords: Management of specific areas; Astronomy, space & time; Nuclear Physics, Heavy Ions, Hadrons; History and Philosophical Foundations of Physics; Particle Acceleration and Detection, Beam Physics; History of Science